2005
DOI: 10.1590/s1516-44462005000300013
|View full text |Cite
|
Sign up to set email alerts
|

Frontal and anterior cingulate activation during overt verbal fluency in patients with first episode psychosis

Abstract: Our preliminary findings of attenuated engagement of inferior prefrontal cortex and anterior cingulate gyrus in patients with recent onset psychosis during phonological verbal fluency are consistent with those of previous studies. The greater activation found in other parts of the anterior cingulate gyrus and prefrontal cortex in patients may be related to a compensatory response that is required to maintain normal task performance, and suggests a pattern of disorganized activity of different functional anteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 33 publications
1
23
0
1
Order By: Relevance
“…There was also a significant group difference in ventrolateral prefrontal cortex, but in this region ARMS subject showed greater activation that controls. Previous studies in first episode 32,42,43 or high-risk samples 27 found both reduced and increased activation in this area during similar verbal fluency tasks relative to a baseline scan. Discrepant findings in the literature might be simply due to differences in experimental design, technical differences of fMRI data acquisition, demographic characteristics, generalized cognitive impairment, and functional heterogeneity in subjects at risk for schizophrenia or to other cofounders such as different exposure to medication, head motion, and lack of diagnostic reassessment during the follow-up.…”
Section: Discussionmentioning
confidence: 77%
“…There was also a significant group difference in ventrolateral prefrontal cortex, but in this region ARMS subject showed greater activation that controls. Previous studies in first episode 32,42,43 or high-risk samples 27 found both reduced and increased activation in this area during similar verbal fluency tasks relative to a baseline scan. Discrepant findings in the literature might be simply due to differences in experimental design, technical differences of fMRI data acquisition, demographic characteristics, generalized cognitive impairment, and functional heterogeneity in subjects at risk for schizophrenia or to other cofounders such as different exposure to medication, head motion, and lack of diagnostic reassessment during the follow-up.…”
Section: Discussionmentioning
confidence: 77%
“…Others have found SMA responses during phonation (Colebatch et al, 1991), exhalation (Colebatch et al, 1991) and speech (Murphy et al, 1997;Wise et al, 1999;Riecker et al, 2005) along with the ACC (Barrett et al, 2004;Schaufelberger et al, 2005;Schulz et al, 2005). The greater involvement of the SMA during the repetitive syllable task in contrast with prolonged vowels suggests that SMA activity may be greater during complex movements such as syllable production for speech.…”
Section: Components Of the Phonatory Systemmentioning
confidence: 99%
“…A defect in the frontolimbic system or dorsal "archicortical" trend, which encompasses both the superior frontal and anterior cingulate gyri, has been hypothesized to be critical for the stable execution of internally generated, task relevant, action-oriented behaviors (Bilder and Degreef, 1991;Bilder and Szeszko, 1996;Szeszko et al 2002). Evidence for a genetically mediated defect in this integrated system in schizophrenia could play a role in neuropsychological deficits observed during executive functioning (Szeszko et al 2000;Everett et al 2001), two-choice guessing (Paulus et al 1999), verbal fluency (Schaufelberger et al 2005) and conflict monitoring (Kerns et al 2005).…”
Section: And Healthy Volunteers (Du Boisgueheneuc Et Al 2006)mentioning
confidence: 99%